Capacity Development of Micro, Small, and Medium Scale Enterprise Actors in Tourism Sector using Tourism Digital Literacy Approach in Surakarta Indonesia - Shubuha Pilar Naredia; Argyo Demartoto; Akhmad Romadhon (Proceedings Series on Social Sciences & Humanities, 2023)
Digital platform is an effective strategy to optimize tourism potency. This exploratory research analyzes capacity development of Micro Small And Medium Enterprises (MSMEs) actors in tourism sector using tourism digital literacy approach in Surakarta Indonesia with Parsons’ Structural Functional theory through observation, in-depth interview and related documentation from MSMEs actors in Tourism Sector, Related Service Offices, Manager of Night Market Ngarsopuro and tourists in Surakarta selected using purposive sampling technique. Source triangulation was used for testing data validity and interactive model for data analysis. Socialization is made to MSMEs actors in tourism sector related to RI’s Law Number 11 of 2008 about Information and Electronic Transaction to improve digital literacy on legal frame of online economic activities. Because online media plays an important role in MSMEs development, training and facilitation are provided concerning social media use through various social platforms to produce and develop tourism promotion content in Surakarta.